Mid-Holocene vegetation dynamics in the Tejo River estuary based on palaeobotanical records from Ponta da Passadeira (Barreiro-Setúbal, Portugal) - Gómez-Orellana, Luis; Ramil-Rego, Pablo; Badal, Ernestina; Carrión Marco, Yolanda; Muñoz Sobrino, Castor (Boreas, 2014)
This paper presents the results of pollen and charcoal analyses carried out in the sedimentary formation of Ponta da Passadeira, south of the Tejo River estuary, Portugal. The data provide information regarding the evolution of the coastline and ecosystem of the estuary during the mid and late Holocene. The study focuses on a group of upright woody fossilized tree remains that, together with those identified earlier by García-Amorena et al. (2007), form part of the fossil forest of Ponta da Passadeira. Eight remains were identified as Pinus pinaster, four as Pinus pinea and one as Pinus sp. Two specimens of these species were dated to 6523 and 5805 cal. a BP. Pollen analysis was undertaken in a clay layer located at the same point as the fossil forest, which is currently below sea level; the base of the clay layer was dated to 4906 cal. a BP. The pollen spectra reflect the dynamics of the vegetation that grew on this deposit, whereas the sporopollinic input masks the contribution of the regional vegetation. Wood charcoal remains recovered at an adjacent Final Neolithic settlement were also analysed, and a Pinus sp. specimen was radiocarbon dated to 5050 cal. a BP. The correlation amongst the three records provides key ecological markers for the understanding of the evolution of coastline ecosystems, and helps to clarify and understand the Holocene sea rise on the Atlantic seaboard of Iberia. The geographical location of Ponta da Passadeira is strategic because it enables a more clear definition of the configuration of landscapes that show an inflection point in this area of central Portugal.
APS
Keywords: charcoal analyses; fossil forest; fossilized wood; Pollen analysis; Vegetation dynamics

Expected trends and surprises in the Lateglacial and Holocene vegetation history of the Iberian Peninsula and Balearic Islands - Carrión, José S.; Fernández, Santiago; González-Sampériz, Penélope; Gil-Romera, Graciela; Badal, Ernestina; Carrión-Marco, Yolanda; López-Merino, Lourdes; López-Sáez, José a; Fierro, Elena; Burjachs, Francesc (Review of Palaeobotany and Palynology, 2010)
Recent, high-resolution palaeoecological records are changing the traditional picture of post-glacial vegetation succession in the Iberian Peninsula. In addition to the inﬂuence of Lateglacial and Early Holocene climatic changes, other factors are critical in the course of vegetation development and we observe strong regional differences. The ﬂoristic composition, location and structure of glacial tree populations and communities may have been primary causes of vegetation development. Refugial populations in the Baetic cordilleras would have been a source, but not the only one, for the early Lateglacial oak expansions. From Mid to Late Holocene, inertial, resilient, and rapid responses of vegetation to climatic change are described, and regional differences in the response are stressed. The role of ﬁre, pastoralism, agriculture, and other anthropogenic disturbances (such as mining), during the Copper, Bronze, Iberian, and Roman times, is analysed. The implications of ecological transitions in cultural changes, especially when they occur as societal collapses, are discussed.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Holocene; iberia; palaeobotany; palaeoecology; palaeogeography; quaternary

Vegetation changes and human action from the Neolithic to the Bronze Age (7000–4000 BP) in Alicante, Spain, based on charcoal analysis - Badal, Ernestina; Bernabeu, Joan; VERNET, J. L. (Vegetation History and Archaeobotany, 1994)
Charcoal analysis reveals various palaeo-eco- logical phases from the Neolithic to the Bronze Age. Ag- riculture starts about 7000 B.P. in favourable ecological conditions. Most of the charcoal spectra from sites iin the coast represent thermomediterranean holm-oak forest; those from the inland mountains represent mesome- diterranean holm-oak forest. The Neolithic I Impressed Ware people were the first to clear the forest to plant their crops. This clearance of primary woodland resulted in the development of secondary vegetation of pine woods or scrub. The scrub reached its maximum during the Bell Beaker phase and Bronze Age in the Cova de les Cendres. In the Neolithic II open air sites, the percent- ages of Quercus ilex/coccifera remain high. This may be the result of a different exploitation of the land, or suit- able conditions for the growth and survival of the vegeta- tion.
Keywords: bronze; CHARCOAL ANALYSIS; human impact; Neolithic; Spain